Three positive real numbers p , q , r satisfy
p 1 + q q 1 + r r 1 + p = = = 2 3 5
Find the sum of all possible values of p .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
After you get quadratic equation, you can just do: sum of roots = -b/a = 26/5 = 5.2 (no need to find roots).
Log in to reply
You still need to check that the roots are real valued, and not complex valued. That requires calculating the discriminant, which is the extra step that was taken.
Log in to reply
And also that both the roots are positive!
The question asks for the sum of the roots. If both roots are not real, then the sum cannot be defined (even to be zero).
F r o m f i r s t a n d t h i r d e q u a t i o n s . . q 1 = 2 p − 1 p . . . . . . . . . . ( 1 ) r = 5 − p 1 . . . . . . . . ( 2 ) S u b s t i t u t i n g ( 1 ) a n d ( 2 ) i n t h e s e c o n d e q u a t i o n : − 2 p − 1 p + 5 − p 1 = 3 ⟹ − 2 p 2 + 1 1 p − 5 5 p − p 2 + 2 p − 1 = 3 ∴ − p 2 + 7 p − 1 = − 6 p 2 + 3 3 p − 1 5 T h a t i s 5 p 2 − 2 6 p + 1 4 = 0 . . . . ∴ S u m o f v a l u e s o f p = 5 2 6 = 5 . 2
Problem Loading...
Note Loading...
Set Loading...
From the second equation we have that q = 3 − r 1 .
From the third equation we have that r = 5 − p 1 .
Thus the first equation becomes
p 1 + 3 − 5 − p 1 1 = 2
⟹ p 1 + 1 4 − 3 p 5 − p = 2
⟹ ( 1 4 − 3 p ) + p ( 5 − p ) = 2 p ( 1 4 − 3 p )
⟹ 5 p 2 − 2 6 p + 1 4 = 0 ⟹ p = 1 0 2 6 ± 3 9 6 = 5 1 3 ± 3 1 1 .
Thus there are two possible positive values for p , and they sum to
2 ∗ 5 1 3 = 5 2 6 = 5 . 2 .